Emergence of Vibrio parahaemolyticus serotype O10:K4 in Thailand. (4th February 2023) - Okada, Kazuhisa; Roobthaisong, Amonrattana; Hearn, Suthida Muangnoicharoen; Okada, Pilailuk Akkapaiboon; Doung‐Ngern, Pawinee; Wongboot, Warawan; Nakkarach, Atchareeya; Morita, Masatomo; Kodama, Toshio; Iida, Tetsuya
Abstract: An emerging serotype O10:K4 of Vibrio parahaemolyticus has been predominantly isolated from outbreaks and sporadic cases in China. Herein, we report the first case of infection due to V. parahaemolyticus O10:K4 isolated from a hospitalized patient with acute diarrhea in Thailand. We sequenced the whole genome of the O10:K4 strain and compared it with those of the pandemic O3:K6 strain, O10:K4 strains in China, and other clinical and environmental strains. The results suggested that the O10:K4 strains are not a mere serotype variant diverged from the pandemic O3:K6 strain, confirming that the O10:K4 strain emergence has spread to Southeast Asia.